Fuzzy logic-based synchronization control system of generators under conditions of frequency instability - M. Al-Soud, Mahmoud; M. Eial Awwad, Abdullah; Al-Quteimat, Alaa; Ushkarenko, Oleksandr (Bulletin of Electrical Engineering and Informatics, 2023)
This article focuses on studying and addressing the issue of synchronizing diesel gas generator units (DGGU) in autonomous electric power system (AEPS) in the presence of significant voltage frequency fluctuations. MATLAB models of AEPS are being developed that will enable the study of generator connection procedures while operating under a full load. Fluctuations in the rotation frequency of a diesel gas unit can be simulated by generating a realistic random procedure and adding this random signal to the control circuit. In the present study, the authors simulated the generator synchronization process in the presence of random disturbances. This simulation results indicated that the presence of random voltage frequency fluctuations and a nonzero response time of the circuit breaker (which connects the generator to the bars of the main distribution board) may violate the synchronization conditions and result in significant current surges and voltage sags at the time of synchronization. In the present work, a block diagram of the generator synchronization system is proposed that uses fuzzy logic to control the synchronization process. Software tools were developed using the methods of conceptual simulation to control the generator synchronization process; these tools represent an automated operator working station.